Evidence-based Therapy in Vascular Surgery - Debus, E. Sebastian; Grundmann, Reinhart T. (Springer International Publishing : Imprint: Springer, 2017)
This book is an introduction to quality initiative for vascular surgery and medicine. Originally published in German, the book is written by leading experts who utilise their professional expertise and insight to help raise the level of patient safety, quality of care, and training of junior vascular physicians. This books aims to bring together the best available current treatment and information, including recent guidelines, meta-analyses, and randomised trials to help put evidence-based therapeutic recommendations into practice. Innovative therapeutic treatment options are not currently incorporated within standard procedure, and this book will help physicians include these methods and create more individualised treatment.